Terrorism in Australia: A Psychometric Study into the Western Australian Public Perception of Terrorism - Brooks, David J (2010)
Terrorism is not a new concept, as historically terrorist organisations have used the threat of violence or actual violence to generate fear in individuals, organisations and governments alike. Fear is a weapon and is used to gain political, ideological or religious objectives. Past terrorist attacks have raised concerns around the world, as governments ensured that their anti-terrorism security strategies are adequate. Domestically, Australia upgraded its capacity to respond to terrorism events through security enhancements across many areas and with new initiatives such as the 2002 public counter terrorism campaign. Nevertheless, there has been restricted research into how terrorist events have impacted on the Australian public from a psychometric risk perception perspective. The study used the psychometric risk perception theory, applied to 340 participants, as a benchmark to compare the perception of terrorism risk using its two dimensions of dread and familiarity to risk. The study presented terrorism within a spatial psychometric risk map and found that when compared to other risks, terrorism ranked second highest in terms of dread risk and mid-range in terms of familiarity to risk. Recommendations include the ongoing need to understand public risk perception and directed benefit of public awareness safety campaigns. It is only through such understanding that decision-makers can implement effective safety and security reforms that will benefit both industry and the general community